Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1111/j.1365-313x.1994.00655.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of transcription and mRNA turnover as mechanisms of metabolic repression of α‐amylase gene expression

Abstract: SummaryCarbon metabolites suppress the expression of a-amylase genes in germinating seeds and in suspension-cultured cells of rice. We have used suspension cell culture as a model system to study the mechanisms of metabolic regulation of a-amylase gene expression in rice. Both transcription rate and mRNA stability increased as cells were starved of sucrose; the transcription rate of a-amylase genes in cells starved of sucrose for 24 h was seven times greater than in cells provided with sucrose. The half-life o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 6 publications
2
62
0
Order By: Relevance
“…In sucrose-starved cells, the transcription rate of α-amylase genes was seven times higher compared with cells provided with sucrose. The α-amylase mRNA half-life was less than 1 h in cells provided with sucrose, but increased to 12 h in sucrose-starved cells (Sheu et al, 1994). The sucrose repression of the ATB2 gene described in this paper is unique in the observation that carbohydrate regulation acts at the translational level.…”
Section: Discussionmentioning
confidence: 82%
“…In sucrose-starved cells, the transcription rate of α-amylase genes was seven times higher compared with cells provided with sucrose. The α-amylase mRNA half-life was less than 1 h in cells provided with sucrose, but increased to 12 h in sucrose-starved cells (Sheu et al, 1994). The sucrose repression of the ATB2 gene described in this paper is unique in the observation that carbohydrate regulation acts at the translational level.…”
Section: Discussionmentioning
confidence: 82%
“…In rice germinating embryos and cultured suspension cells, expression of ␣-amylase genes is activated by sugar depletion and repressed by sugar provision (3,5,6). An increase in both the transcription rate and mRNA half-life under sucrose depletion contributes to the increase in the steady-state level of ␣-amylase mRNA (7,8). Studies in transgenic rice confirmed that the ␣-amylase gene promoters control sugar-dependent repression of reporter gene expression (9)(10)(11).…”
mentioning
confidence: 74%
“…Transcription and mRNA stability are both important mechanisms for Glc repression of ␣-amylase in rice (Sheu et al, 1994); (b) leaf rbcL mRNA may not be as efficiently translated as is rbcS mRNA, or large subunit protein may simply accumulate in excess of small subunit protein, as apparently occurs in tomato (Van Oosten and Besford, 1995), or be degraded (although the latter has not been shown to occur in any system [Rodermel et al, 1996]); and (c) Rubisco protein turnover may be altered such that protein levels are not repressed to an extent comparable to rbcS mRNA. That Rubisco protein may be longer-lived was also suggested in a study of wheat leaves of intermediate age grown at high CO 2 (Webber et al, 1994).…”
Section: Discussionmentioning
confidence: 99%